Instrumentos de avaliação dos eventos adversos associados ao uso de fraldas geriátricas - Graziele Ribeiro Bitencourt; Rosimere Ferreira Santana (Universidade Federal do Ceará, 2019)
Objective to analyze instruments for the evaluation of adverse events associated with the use of geriatric diapers.Methods integrative review of the literature, in the LILACS, MEDLINE, CINAHL and EMBASE databases, with publications in Portuguese, English and Spanish. In the analysis of the data, categorization occurred by the identification of adverse events and screening instruments.Results of the 19 publications, we identified as adverse events and respective instruments: motor deficit/Barthel index; Incontinence/Kings's Health Questionnaire and International Consultation on Incontinence Questionnaire-Short Form; skin moisture/Transepidermal Water Loss; quality of life/Hospital Anxiety and Depression Scale; incontinence-associated dermatitis/Nix Perineal Rating Scale.Conclusion instruments were analyzed that evaluated the adverse events associated with the use of diapers that may be potentially used in nursing practice.